Factors affecting UPV-CM undergraduate students' usage of informal learning spaces in a University City Iloilo City - Bayawa, Sweetzel M.; besana, Kana Lou Cassandra B.; Cariaga, Neil Ryan U.; Ladrido, Bryan Jay O.; Patoc, Candy Anne R.
Students' behavior and needs in relation to learning have changed over the years. Because of this, learning spaces, specifically informal learning spaces have evolved to cater the needs of the growing population of students and even young professionals who usually prefer to do their work outside their classroom or offices. Also, most of these informal learning spaces today are typically located near university cities. Basically, the purpose of this study is to determine the factors that affect the University of the Philippines Visayas-College of Management undergraduate students' usage of informal learning space in Iloilo City and to rank these factors based on their impact on students' usage of informal learning spaces. The independent variables of the study are the students' personal profile, their learning preferences and their perception of environmental factors while the students' usage of informal learning spaces is the dependent variable. With this in mind, the researchers conducted a survey and used the Statistical Package for the Social Sciences (SPSS) and excel as statistical tools to generate the results of this study from the data collected. based from the analysis of the results, the researchers have concluded that UPV-CM undergraduate students uses Boarding House/ Dormitory/ Home most frequently as informal space for academic purpose with a mean score of 4.47. It was also found out that personal profiles such as course, allowance, GWA, age sex, and location of residence have significant correlations towards the students' learning preferences in activity and group size. Also, personal profile like course, GWA, academic units, sex, and residence have significant correlations toward the students' perception of environmental factors. Lastly, the researchers have found out that the students' personal profile ranked first as the factor that significantly affects the usage of informal learning spaces followed by the students' perception of environmental factors while, on the other hand, their learning preferences in terms of activity and group size have no significant effect on their usage of informal learning spaces.